Effectiveness of a physical activity program among overweight and obese women - Öznur Özkan Bambal; Pınar Erbay Dündar; Gürkan Er; Özgür Bayturan (Turkish Society of Public Health Specialists, 2015)
Abstract Objective: This study evaluates the impact of a physical activity (PA) intervention program on body composition and anthropometrical measurements among middle aged, overweight and obese women. Methods: This was an interventional study in a semi-urban area. Sample size was calculated as 85 women for each group. The overweight and obese women were assigned to one of two groups by randomization on the basis of a cross-sectional study. Women from both groups participated in a training program on healthy life styles. The intervention group participated in a PA program for three months, three times a week. Anthropometrical and bioelectrical impedance analysis (BIA) measurements were performed at the beginning and repeated on 6th and 12th weeks for each group. The Chi square test, Fisher's exact test, Student's T test and variance analysis on repeated measures were used for data analysis. Results: Intervention and control groups were similar at the baseline evaluation in terms of their socio-demographic and BIA characteristics. There were statistically significant decreases in both groups in terms of BIA indicators, while body fat percent and trunk fat weight remained unchanged in the control group. When reductions between first and last measurements were compared, for all BIA indicators except for maximum effort capacity scores, muscle weight and body fat percent; the differences were statistically significant in the intervention group. Reductions in body weight, BMI and waist circumference for women who participated in 30 or more PA sessions were higher than for those who participated in 29 or fewer sessions. Conclusions: This PA intervention program was effective for middle aged overweight or obese women in terms of improvement on anthropometrical determinants of obesity. This intervention program can be offered as an appropriate model for similar groups. Key Words: Obesity, intervention study, health promotion, physical activity.